Identifikasi Dan Pola Penempatan Kuburan Tionghoa Di Bali - Gendro Keling; Muhamad Nofri Fahrozi; Indria, Ida Ayu Gede Megasuari (Badan Riset dan Inovasi Nasional (BRIN), 2025)
Chinese society believes in the existence of human relations with God or other powers that control human’s life, such as reincarnation and the law of karma for all human actions. This is reflected in rites and Chinese Cemeteries. Chinese Cemeteries are considered a bridge that connects the human realm with ancestral spirits in the sky. This article attempts to reveal the socio-religious aspects of Chinese Cemeteries in Bali. Data collection is done by observation and literature study. The data was analysed by using stylistic and contextual analysis. The results show that Chinese Cemeteries in Bali, especially in the bongpay section contain some information about the identity of the dead, starting from the name and surname of the dead, time of death, origin of the dead, and closest relatives of the dead. In addition, the placement location of Chinese Cemeteries in Bali also contains a specific purpose, namely its relation to feng shui in the hope of providing good benefits for the dead and good wishes for the dead's family who are still alive.